Determinan Perilaku Ibu Hamil Dalam Melakukan Pemeriksaan Tripel Eliminasi - Istiana Kusumastuti; Hari Ghanesia Istiani (Universitas Muhammadiyah Pekajangan Pekalongan, 2024)
ABSTRACT HIV, Syphilis and Hepatitis infections are infectious diseases that are still a health problem in the world, including in Indonesia. The incidence of transmission from mother to child ranks highest in the incidence of transmission in these 3 diseases. The purpose of this study was to determine the magnitude of the variable influence of information sources, the role of midwives, husband support, knowledge of maternal behavior in conducting triple elimination checks. This research method is Quantitative with cross sectional design with the analysis method used is SPSS. The sample of this study were all pregnant women with a total of 108. The results of the study using chi square on the variables of information sources, the role of midwives, husband support and knowledge have a significant influence on maternal behavior in conducting Triple Elimination checks where all variables have a p-value smaller than the provisions of 0.05. Based on the OR results of all variables, it can be seen that the information source variable has the greatest influence on maternal behavior in triple elimination checks in the Jabodetabek region, which is 4,870 times influential. It is recommended that education and information are continuously given to pregnant women. Keywords: Behavior, Examination, Triple Elimination